Relationship between Interest in Learning with Children's Learning Outcomes in Kindergarten Aisyiyah Bustanul Athfal Salido - Siti Nur Ajizah; Regina Aprilia Rusliana; Oktraliza Chania; Mega Meisisrika Aldi (Universitas Negeri Padang, 2019)
The purpose of this study is to find out and describe children's interest in learning and learning outcomes, after participating in learning activities. Changing children's interest in learning is not easy, especially in early childhood, wherein early childhood the mind is just playing we as parents and teachers must be good at increasing children's interest in learning by stopping to force our will, what we want is not necessarily the child wants. Forcing children to learn makes children afraid and tense and causes children to get frustrated quickly. And look for the right socialization for the child so he wants to study. while children's learning outcomes, In general, there are two factors that affect student learning outcomes, namely there are internal and external factors, where student learning interest which is included in one of the internal factors also has a close relationship with student learning outcomes, lack of student interest causes low results student learning. These learning outcomes there is a positive relationship between learning interest with student learning outcomes. Keywords: Interest in Learning, Learning Outcomes